What do peer support workers do? A job description - Jacobson Nora; Trojanowski Lucy; Dewa Carolyn S (BMC, 2012)
Abstract Background The extant literature suggests that poorly defined job roles make it difficult for peer support workers to be successful, and hinder their integration into multi-disciplinary workplace teams. This article uses data gathered as part of a participatory evaluation of a peer support program at a psychiatric tertiary care facility to specify the work that peers do. Methods Data were gathered through interviews, focus groups, and activity logs and were analyzed using a modified grounded theory approach. Results Peers engage in direct work with clients and in indirect work that supports their work with clients. The main types of direct work are advocacy, connecting to resources, experiential sharing, building community, relationship building, group facilitation, skill building/mentoring/goal setting, and socialization/self-esteem building. The main types of indirect work are group planning and development, administration, team communication, supervision/training, receiving support, education/awareness building, and information gathering and verification. In addition, peers also do work aimed at building relationships with staff and work aimed at legitimizing the peer role. Experience, approach, presence, role modeling, collaboration, challenge, and compromise can be seen as the tangible enactments of peers' philosophy of work. Conclusions Candidates for positions as peer support workers require more than experience with mental health and/or addiction problems. The job description provided in this article may not be appropriate for all settings, but it will contribute to a better understanding of the peer support worker position, the skills required, and the types of expectations that could define successful fulfillment of the role.